Longitudinal development of manual motor ability in autism spectrum disorder from childhood to mid‐adulthood relates to adaptive daily living skills. Issue 4 (7th April 2016) - Travers, Brittany G.; Bigler, Erin D.; Duffield, Tyler C.; Prigge, Molly D.B.; Froehlich, Alyson L.; Lange, Nicholas; Alexander, Andrew L.; Lainhart, Janet E.
Abstract: Many individuals with autism spectrum disorder (ASD) exhibit motor difficulties, but it is unknown whether manual motor skills improve, plateau, or decline in ASD in the transition from childhood into adulthood. Atypical development of manual motor skills could impact the ability to learn and perform daily activities across the life span. This study examined longitudinal grip strength and finger tapping development in individuals with ASD ( n  =   90) compared to individuals with typical development ( n  =   56), ages 5 to 40 years old. We further examined manual motor performance as a possible correlate of current and future daily living skills. The group with ASD demonstrated atypical motor development, characterized by similar performance during childhood but increasingly poorer performance from adolescence into adulthood. Grip strength was correlated with current adaptive daily living skills, and Time 1 grip strength predicted daily living skills eight years into the future. These results suggest that individuals with ASD may experience increasingly more pronounced motor difficulties from adolescence into adulthood and that manual motor performance in ASD is related to adaptive daily living skills. Abstract : We investigated age‐related changes from early childhood into mid‐adulthood in manual motor skills in individuals with autism spectrum disorder (ASD) compared to typical development. We then examined if manual motor performance correlated with current and future daily living skills. We found evidence for atypical development of grip strength and finger tapping speed in ASD, atypically low grip strength in ~1/3 of the individuals with ASD, and correlations between manual motor performance and both current and future daily living skills.